2022
DOI: 10.1002/ejoc.202200539
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Isomerization of Unprotected Mesoionic N‐Heterocyclic Olefins and Their Lewis Adducts

Abstract: Recently, novel C 5 -position-unprotected mesoionic N-heterocyclic olefins (mNHOs) demonstrated interesting reactivity with various Lewis acids during experiments. In this work, extensive DFT calculations show that the isomerization of such mNHOs to more Lewis-basic mesoionic carbenes (MICs) can be efficiently catalyzed by weakly protic acidic species including C 5 -unprotected mNHOs, their Lewis adducts and polar H 2 O molecules, thus enabling catalytic isomerization and H-isotope exchange of such mNHOs and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 37 publications
1
7
2
Order By: Relevance
“…When very small dihydrogen is used as substrate for catalytic H 2 isotope exchange, the dimeric mechanism becomes more important due to evidently reduced steric hindrance and stronger dinuclear cooperative effects. As seen in Figure 3(A), according to our recent DFT calculations, a very facile H•••H•••Htype H 2 isotope exchange may occur via a cooperative CaÀ HÀ Ca bridge of THF-free cation dimer 1 2 + over a low barrier of 16.9 kcal mol À 1 (via TS5 2 + ) after THF elimination, [14] consistent with the very fast reaction observed at room temperature. [10] The three exchanging hydrogen atoms are placed evenly between two calcium ions and perpendicular to the other CaÀ HÀ Ca bridge, suggesting potentially strong dinuclear cooperative effects.…”
Section: Chemistryopensupporting
confidence: 82%
See 3 more Smart Citations
“…When very small dihydrogen is used as substrate for catalytic H 2 isotope exchange, the dimeric mechanism becomes more important due to evidently reduced steric hindrance and stronger dinuclear cooperative effects. As seen in Figure 3(A), according to our recent DFT calculations, a very facile H•••H•••Htype H 2 isotope exchange may occur via a cooperative CaÀ HÀ Ca bridge of THF-free cation dimer 1 2 + over a low barrier of 16.9 kcal mol À 1 (via TS5 2 + ) after THF elimination, [14] consistent with the very fast reaction observed at room temperature. [10] The three exchanging hydrogen atoms are placed evenly between two calcium ions and perpendicular to the other CaÀ HÀ Ca bridge, suggesting potentially strong dinuclear cooperative effects.…”
Section: Chemistryopensupporting
confidence: 82%
“…[14] In benzene solution, the dimer [(THF)(BDI)CaH] 2 was computed to be about 7.7 kcal mol À 1 higher in free energy than two (THF)(BDI)CaH monomers, [15] in sharp contrast to previous experimental [1c] and our recent dispersion-corrected DFT results (À 18.2 kcal mol À 1 lower dimer than two monomers). [14] It is thus crucial to include both dispersion corrections and suitable solvation in modeling such catalytic reactions in solution.…”
Section: Resultscontrasting
confidence: 63%
See 2 more Smart Citations
“…[13] In addition, Melen and co-workers have reviewed borane mediated carbene transfer reactions using diazomethanes, [14] while more recently carbocations derived from protonation of diazomethane α-carbon atoms were shown to be key intermediate in such reactions. [15] In 2018, the seminal report by Braunschweig et al [16] demonstrated N 2 reduction by a B I species. To us, this further supported the notion that similar reactivity might also be achieved with a B III species and a two-electron donor (i.e., a FLP).…”
mentioning
confidence: 99%